Retention Strategies for Medications for Opioid Use Disorder in Adults: A Rapid Evidence Review. Issue 1 (January 2021) - Chan, Brian; Gean, Emily; Arkhipova-Jenkins, Irina; Gilbert, Jennifer; Hilgart, Jennifer; Fiordalisi, Celia; Hubbard, Kimberly; Brandt, Irene; Stoeger, Elizabeth; Paynter, Robin; Korthuis, Philip Todd; Guise, Jeanne-Marie
Abstract : Objectives: Although medications for opioid use disorder (MOUD) save lives, treatment retention remains challenging. Identification of interventions to improve MOUD retention is of interest to policymakers and researchers. On behalf of the Agency for Healthcare Research and Quality, we conducted a rapid evidence review on interventions to improve MOUD retention. Methods: We searched MEDLINE and the Cochrane Library from February 2009 through August 2019 for systematic reviews and randomized trials of care settings, services, logistical support, contingency management, health information technology (IT), extended-release (XR) formulations, and psychosocial interventions that assessed retention at least 3 months. Results: Two systematic reviews and 39 primary studies were included; most did not focus on retention as the primary outcome. Initiating MOUD in soon-to-be-released incarcerated people improved retention following release. Contingency management may improve retention using antagonist but not agonist MOUD. Retention with interventions integrating medical, psychiatric, social services, or IT did not differ from in-person treatment-as-usual approaches. Retention was comparable with XR- compared to daily buprenorphine formulations and conflicting with XR-naltrexone monthly injection compared to daily buprenorphine. Most psychosocial interventions did not improve retention. Discussion: Consistent but sparse evidence supports criminal justice prerelease MOUD initiation, and contingency management interventions for antagonist MOUD. Integrating MOUD with medical, psychiatric, social services, delivering through IT, or administering via XR-MOUD formulations did not worsen retention. Fewer than half of the studies we identified focused on retention as a primary outcome. Studies used different measures of retention, making it difficult to compare effectiveness. Additional inquiry into the causes of low retention would inform future interventions. Registration: PROSPERO: CRD42019134739 Abstract : Supplemental Digital Content is available in the text